The enhanced performance of CFST beams using different strengthening schemes involving unidirectional CFRP sheets: An experimental study. (1st December 2016) - Al Zand, Ahmed W.; Badaruzzaman, Wan Hamidon W.; Mutalib, Azrul A.; Hilo, Salam J.
Highlights: Establishing a sufficient strengthening scheme of CFST beams using CFRP sheets. Combined, full, and partial strengthening schemes' effects were compared experimentally. CFRP have significantly improved the CFST beam's capacity, stiffness and energy absorption. Partial and full strengthening schemes have achieved similar loads enhancements. Beams with 75% and 100% strengthening length have achieved similar loads enhancements. Abstract: Concrete-filled steel tube (CFST) beam, like any conventional structural member, for several reasons need strengthening, such as by making upgrades to carry extra loads or to make repairs owing to degradation attributed to aging, fire, and fatigue. This study experimentally investigates the strengthening behaviour of the circular and rectangular simply supported CFST beams using unidirectional carbon fibre reinforced polymer (CFRP) sheets, in which partial-unilateral (partial), full-unilateral (full), and full-bilateral (combined) strengthening schemes with varied layers and lengths are used. The results show that the moment capacity, energy absorption capacity, and flexural stiffness of the strengthened beam significantly improved with the increase of CFRP layers. For example, the moment capacity of the rectangular beams increased by about 26% and 38% when they were partially strengthened with two and three CFRP layers, respectively. Also, the beams were partially strengthened with two CFRP layers laid along 75% and 100% of their lengths, and that fully strengthened along 100% of its length, all achieved almost the same load improvements (+26% to +28%) in comparison with their control beam, which means that about 50% of the amount of CFRP sheets or even more can be saved and the same improvement can be achieved. The energy absorption capacity of the circular beams improved by about 21.8% when they were partially strengthened with two CFRP sheets, for example. Moreover, the flexural stiffness values of the strengthened beams fairly agreed with those predicted from the existing standards (AISC, EC4, BS5400, and AIJ) after including the effects of CFRP.